The Effectiveness of Application Mediation in Reducing Divorce Cases at Jombang Religious Court - Muhammad Amin Syarifudin; Herwastoeti Herwastoeti; Dwi Ratna Indri Hapsari (Indonesia Law Reform Journal, 2022)
The reason for the occurrence of divorce at the Jombang Religious Court is due to several factors, but in how many years the pandemic has increased other factors such as a moral crisis, no responsibility, persecution, biological defects, economic problems, and other factors, jealousy, forced marriage, and no household harmony and underage marriage, divorce is a legal way to deal with marital conflicts under the umbrella of Indonesian law and formalized Islamic law, it is hoped that mediation will be the mediating point of all kinds of divorce issues, Mediation is a process of judicial proceedings regulated in PERMA No. 1 of 2016 concerning mediation procedures in court. the implementation of mediation at the Jombang Religious Court has been carried out according to the procedure, but in the last 4 years the Jombang Religious Court has experienced an increase in cases and the number that cannot be mediated is quite a lot due to the absence of the parties even though they have been summoned more than twice but the parties still choose not present so that the case continues and cannot be mediated, while cases that can be mediated are influenced by the peaceful intentions of both parties so that the mediation can be carried out or those who are being mediated choose to come because they demand their rights as in the case of divorce talk is alimony arising from divorce, so the authors found the ineffectiveness of mediation in its implementation which was unsuccessful due to several obstacles in its implementation, namely the strong desire between parties, ignorance of the importance of mediation by the community, the role of advocates. The author also provides a solution to the obstacles to the ineffectiveness of mediation by maximizing the panel of judges, mediation training, the role of the mediator, the role of the government, and evaluating the performance of the mediator.